Sistem Pendukung Keputusan Penentuan Profesi Mahasiswa Informatika Menggunakan Metode WP-RIASEC - Raihan Aqila Taufik; Miftahurrahma Rosyda (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Informatic Program in Ahmad Dahlan University engaged in the field of informatics/computer science. At the Informatic Program in Ahmad Dahlan University, there are still many students who are confused when they want to decide which profession to pursue when they graduate. This is based on a questionnaire distributed to final semester students from the Informatics Program in Ahmad Dahlan University. From the distributed questionnaires, the results of the questionnaire were obtained, namely more than 50 percent of respondents were still confused in determining the professional field to be occupied when they graduated. In addition, in an interview conducted with a psychologist, he said that personality is very influential on a person's work. To help Ahmad Dahlan University Informatics Students in determining a profession, a decision support system was created that can help students of the department in determining the appropriate professional field based on the value of the course and their personality. The method used in this research is WP and RIASEC. The WP method plays a role in calculating the weight of each course value. While the RIASEC method plays a role in determining a person's personality which is the basis for determining appropriate professional alternatives based on their personality. The results of system testing that have been carried out on 10 respondents consisting of 7 students and 3 alumni from the Informatics Program in Ahmad Dahlan University have obtained test results with a value of 84.5, which means the system is running well and meets the existing standards.